Ectomycorrhizal Fungi of Salix Rotundifolia Trautv. I. Impact of Surface Applied Prudhoe Bay Crude Oil on Mycorrhizal Structure and Composition - Antibus, R.K.; Linkins, A.E. (ARCTIC, 1978)
The effects of exposure to crude oil on the structure and quantity of viable mycorrhizae of the dwarf deciduous shrub, Salix rotundifolia Trautv., have been investigated at Barrow and Cape Simpson, Alaska over a three year period on experimental plots treated with 5 and 12 l/m² of Prudhoe Bay crude oil. Salix rotundifolia populations growing adjacent to the Cape Simpson natural oil seep were examined for possible changes which may have occurred as the result of long term exposure to oil. Structural examination of mycorrhizae was accomplished by light and scanning electron microscopy. Structural difference in viable mycorrhizae were observed between control and oil treated plots one year after the application of oil. Ectomoycorrhizae with smooth mantle surfaces were found to predominate on the Barrow control plot. The predominant viable mycorrhizae on the oil treated plots demonstrated a marked proliferation of mantle hyphae, presumably a result of the altered soil environment. Prudhoe Bay crude oil applied at 12 l/m² caused a large reduction in the number of viable willow mycorrhizae within one week at Barrow. After this rapid initial response, the rate of destruction of mycorrhizae appeared to proceed at a slower rate throughout the remainder of the growing season. The effect of oil in depressing the number of viable mycorrhizae was still apparent three growing seasons after the application of oil. Salix rotundifolia growing adjacent to the Cape Simpson oil seep demonstrated greater numbers of viable mycorrhizae and a higher percentage of Cenococcum graniforme (Sow.) Ferd and Winge. mycorrhizae than did plants at Barrow.